Annals of photodynamic therapy: Publish and/or Perish? - David Kessel (Photodiagnosis and Photodynamic Therapy, 2024)
The current situation with regard to journal publishing is markedly different from the days when everything was done by mail and subscriptions paid the costs. In even earlier times, i.e., the era of Darwin, scientists tended to publish their findings in book form only after prolonged investigations. Now, publishing is Big Business, scavengers troll the internet for evidence of questionable data to report, significant numbers of CHF can be exchanged for access to journals and reviewing can be hazardous. In the era of the internet, appearance of a report with significant errors missed by reviewers can lead to ‘publish AND perish’.